Digital Transformation for Operational Leverage: Perception of Small Business Entrepreneurs in Nepal - Bhatt, Shankar Datt; Subedi, Khem Raj (The Management Review, 2026)
The global business landscape is transforming rapidly with the cutting edge of advanced digital technology as an outcome of the Fourth Industrial Revolution. The aim of this paper is to assess the perceived influence of digital transformation (DT) on overall operational leverage of small business entities and identify challenges and barriers in the process of DT in the study area of Kailali and Kanchanpur districts. The philosophical underpinning of this paper is a pragmatic realist ontological lens implying that DT in SBFs is both an observable and measurable phenomenon. in terms of selected dimensions and constructs in the context of business performance appraisal. The study population is defined as all the SBFs operating in the study area that are divided into 11 strata and the purposive sampling technique was adopted within the strata considering the relevancy of the study objective. The findings revealed that digital transaction proportion is about 37 percent of total transaction, followed by a 13.99 percent increase in perceived operational efficiency, an 11.16 percent reduction in perceived operational cost, and a 14.58 percent growth in perceived sales. Moreover, DT reduces marginal transaction cost, and improves allocative efficiency, thereby enhancing productivity of SBFs. In conclusion, DT is instrumental in contributing significantly to increase overall operational efficiency and enhancing performance and competitiveness of SBFs. Therefore, the policy makers and stakeholders are expected to focus on encouraging DT in the business operation through digital literacy and financial incentives for SBFs.